Science, the Self, and Survival After Death, Selected Writings of Ian Stevenson, edited by Emily Williams Kelly - Haraldsson, Erlendur (Journal of Scientific Exploration, 2014)
Reading this book, I could not help comparing it with another covering some of the same ground, which I had read recently, namely, A Universe from Nothing: Why There Is Something Rather than Nothing by Lawrence M. Krauss (2012). Each author has an agenda. Krauss wishes to persuade us that the universe will arise from nothing quite naturally, without any need for a Divine Creator, while Wolf wishes to persuade us that consciousness determines reality and that the very same phenomena that led Krauss to atheism actually provide evidence for the existence of a Divine mind at the heart of everything. Each author attempts the difficult task of explaining quantum-field theory in non-technical terms in order to bolster his case, but they draw diametrically opposed conclusions from the physical data. In my opinion, Krauss’ argument fails because it is circular, but his book is not under review here and I shall not go into details. Wolf is more subtle and low-key in his presentation. Despite the subtitle, and apart from some tantalizing references to the Vedic scriptures and a few scattered mentions in the body of the book, God does not make an appearance until the last chapter. There, Wolf presents us with his own personal interpretations, but he makes no claim to have provided a scientific proof of the existence of God and freely acknowledges that many of his colleagues will disagree with him.